ECG changes in factory workers exposed to 27.2 MHz radiofrequency radiation. Issue 4 (31st December 2012) - Chen, Qingsong; Xu, Guoyong; Lang, Li; Yang, Aichu; Li, Shilin; Yang, Liwen; Li, Chaolin; Huang, Hanlin; Li, Tao
Abstract To research the effect of 27.2 MHz radiofrequency radiation on electrocardiograms (ECG), 225 female workers operating radiofrequency machines at a shoe factory were chosen as the exposure group and 100 female workers without exposure from the same factory were selected as the control group. The 6 min electric field strength that the female workers were exposed to was 64.0 ± 25.2 V/m (mean ± SD), which exceeded 61 V/m, the International Commission on Non‐Ionizing Radiation Protection reference root mean square levels for occupational exposure. A statistical difference was observed between the exposed group and the control group in terms of the rate of sinus bradycardia (χ2 = 11.48, P = 0.003). When several known risk factors for cardiovascular disease were considered, including smoking, age, alcohol ingestion habit, and so on, the exposure duration was not an effective factor for ECG changes, sinus arrhythmia, or sinus bradycardia according to α = 0.05, while P = 0.052 for sinus arrhythmia was very close to 0.05. We did not find any statistical difference in heart rate, duration of the QRS wave (ventricular depolarization), or corrected QT intervals (between the start of the Q wave and end of the T wave) between the exposed and control groups. Occupational exposure to radiofrequency radiation was not found to be a cause of ECG changes after consideration of the confounding factors. Bioelectromagnetics 34:285–290, 2013. © 2012 Wiley Periodicals, Inc.